2009
DOI: 10.1215/15228517-2009-004
|View full text |Cite
|
Sign up to set email alerts
|

DC vaccination with anti-CD25 treatment leads to long-term immunity against experimental glioma

Abstract: We studied the feasibility, efficacy, and mechanisms of dendritic cell (DC) immunotherapy against murine malignant glioma in the experimental GL261 intracranial (IC) tumor model. When administered prophylactically, mature DCs (DCm) ex vivo loaded with GL261 RNA (DCm-GL261-RNA) protected half of the vaccinated mice against IC glioma, whereas treatment with mock-loaded DCm or DCm loaded with irrelevant antigens did not result in tumor protection. In DCm-GL261-RNA-vaccinated mice, a tumor-specific cellular immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 65 publications
(71 reference statements)
4
101
0
Order By: Relevance
“…To generate intra-brain GBM, the mice were intra-axially injected with 5£10 5 GL261 cells as described previously. 47 In brief, mice were anesthetized, set in a stereotactic frame (Kopf Instruments) and injected (in sterile circumstances) with the GL261 cells at 2 mm lateral and 2 mm posterior from the bregma, and at 3 mm underneath the dura mater. After intrabrain inoculation, the mice were monitored 2-3 times per week and clinical symptoms were noted with a neurologic-deficit grading scale modified from an experimental autoimmune encephalomyelitis model, described in the past.…”
Section: Methodsmentioning
confidence: 99%
“…To generate intra-brain GBM, the mice were intra-axially injected with 5£10 5 GL261 cells as described previously. 47 In brief, mice were anesthetized, set in a stereotactic frame (Kopf Instruments) and injected (in sterile circumstances) with the GL261 cells at 2 mm lateral and 2 mm posterior from the bregma, and at 3 mm underneath the dura mater. After intrabrain inoculation, the mice were monitored 2-3 times per week and clinical symptoms were noted with a neurologic-deficit grading scale modified from an experimental autoimmune encephalomyelitis model, described in the past.…”
Section: Methodsmentioning
confidence: 99%
“…Murine DC were produced based on existing protocols (16)(17)(18). The mice were euthanized by cervical dislocation.…”
Section: Methodsmentioning
confidence: 99%
“…Thus immunotherapeutic strategies for treating metastatic CNS tumors must fight against Treg (Sugihara, et al 2009). In an experimental GL261 intracranial tumor model, it was shown that depletion of CD25(+) regulatory T-cells (Treg) using anti-CD25 antibodies enhance the efficacy of DC immunotherapy (Maes, et al 2009). Infiltration of myeloid suppressor cells (MSC) is another factor inhibiting the function of the CD8(+) T cells, which results in tumour progression (Graf, et al 2005).…”
Section: T Cell Infiltration In Tumours and Prognosismentioning
confidence: 99%